O trabalho educativo com o software de geometria dinâmica no quinto ano do ensino fundamental - Souza, Viviane Aparecida de (2017)
In this research we try to understand the feasibility of working with Dynamic Geometry software in the process of teaching and learning geometry in the fifth year of elementary school in a public school. This research project was funded by the Minas Gerais Research Support Foundation (FAPEMIG), in partnership with the Coordination of Improvement of Higher Education Personnel (CAPES), and 30 students were invited to attend the fifth year of primary education , In the years 2014 and 2015, totaling 60 students and two teachers regents of the classes. Also a group of researchers participated, which formalized a collective work, whose purpose was to seek differentiated strategies of teaching and learning about the use of technologies in pedagogical practice. This team was composed by a graduate of the Mathematics Degree course of the Federal University of Uberlândia, a Master in Mathematics Education, two Masters of Science and Mathematics from UFU who studied different years, including the researcher of this study and also a laboratory Of the researched school and the professor doctor advisor. This study is characterized as action research and has a qualitative approach. The process of producing information occurred through the following strategies: lessons recorded in videos and transcribed; Field notes produced by the researcher; Application of questionnaires and interviews and analysis of student interventions on different blogs. In this research we analyze the activities implemented in a given software by the students, observing the visualization, the types of possible representations, being: graphic, natural language, algebraic writing and figure. In addition to making relations with the types of seizures (sequential, perceptive, discursive and operative) based on Duval's theory. It is concluded that this educational practice with this software is feasible for students of this age group and that it is possible to develop differentiated and stimulating activities that help students in building their knowledge about geometry.